46‐3: Distinguished Paper: 4032ppi High‐Resolution OLED Microdisplay. Issue 1 (30th May 2018) - Fujii, Takuma; Kon, Chiaki; Motoyama, Yosuke; Shimizu, Kan; Shimayama, Tsutomu; Yamazaki, Takashi; Kato, Takayoshi; Sakai, Seigou; Hashikaki, Koichi; Tanaka, Koji; Nakano, Yasuhiro
Abstract : A 0.5 inch UXGA OLED microdisplay has been developed with 6.3μm pixel pitch. Not only 4032ppi high resolution, but high frame rate, low power consumption, wide viewing angle and high luminance have been achieved. This newly developed OLED microdisplay is suitable for Near‐to‐Eye display applications, especially electronic viewfinders.